Convection-Enhanced Delivery of AAV2-PrPshRNA in Prion-Infected Mice - Ahn, Misol (Public Library of Science, 2014)
Prion disease is caused by a single pathogenic protein (PrP(Sc)), an abnormal conformer of the normal cellular prion protein PrP(C). Depletion of PrP(C) in prion knockout mice makes them resistant to prion disease. Thus, gene silencing of the Prnp gene is a promising effective therapeutic approach. Here, we examined adeno-associated virus vector type 2 encoding a short hairpin RNA targeting Prnp mRNA (AAV2-PrP-shRNA) to suppress PrP(C) expression both in vitro and in vivo. AAV2-PrP-shRNA treatment suppressed PrP levels and prevented dendritic degeneration in RML-infected brain aggregate cultures. Infusion of AAV2-PrP-shRNA-eGFP into the thalamus of CD-1 mice showed that eGFP was transported to the cerebral cortex via anterograde transport and the overall PrP(C) levels were reduced by ∼70% within 4 weeks. For therapeutic purposes, we treated RML-infected CD-1 mice with AAV2-PrP-shRNA beginning at 50 days post inoculation. Although AAV2-PrP-shRNA focally suppressed PrP(Sc) formation in the thalamic infusion site by ∼75%, it did not suppress PrP(Sc) formation efficiently in other regions of the brain. Survival of mice was not extended compared to the untreated controls. Global suppression of PrP(C) in the brain is required for successful therapy of prion diseases.